Pemanfaatan Digital Marketing dalam Industri Perhotelan di Kota Medan - Dewi Yanti (Jurnal Ilmiah Akomodasi Agung, 2019)
Medan is the third largest city in Indonesia and making Medan one of the destinations for visiting business and tourism activists. To support these activities, the role of the hotel is usually needed for tourists visiting an area. Based on the North Sumatra Central Bureau of Statistics the percentage of room occupancy rates in the city of Medan, the highest average is a four-star hotel. Some four-star hotels in Medan (Adimulia, Four Points, Emerald Garden and Santika Hotels) utilize digital marketing to promote and increase occupancy rates in managed hotels. This research uses qualitative methods, by collecting various data sources through observation and literature study. The results of this study indicate that by utilizing digital marketing, hotels can increase the number of visits through reviews provided by visitors to increase the hotel profile.